Results of Experimental Studies on the Selection of the Optimal Ridger Type for the Combined Machine - Nazirjonov, I. A.; Xudoyarov, A. N.; Yuldasheva, M. A. (American Journal of Biodiversity, 2025)
The article presents the results of tests conducted to select the type of ridge former for a combined machine. As a result, the furrow opener of the KXM-4 cultivator was selected for ridge formation while ensuring minimal energy consumption and meeting the required performance criteria. The selected furrow opener was then improved and adopted for further research.